The influence of spousal care on the health of middle-aged and older adult caregivers in China—empirical analysis based on CHARLS data - Rui Wang (Frontiers in Public Health)
ObjectivesWith the decrease of the number of children and the increase of population mobility, child care presents a phenomenon of “double shortage” of human and time resources, and spousal care is becoming an important care source for middle-aged and older adult people in China. However, less studies have taken middle-aged and older adult couples as research subject to explore the health effects of spousal care in the process of aging. This paper attempts to explore the effects of caregiving on the health of caregivers from the perspective of spousal care.MethodsUsing China Health and Retirement Longitudinal Study (CHARLS) database, this paper constructs a panel data fixed effect model to explore the effects of spousal care on the health of middle-aged and older adult caregivers. Further, instrumental variables (IV) estimation and propensity score matching (PSM) are used to minimize the impacts of endogeneity.ResultsSpousal care has no significant effect on the physical health of middle-aged and older adult caregivers, but it has a significant negative effect on their mental health. Providing spousal care has a stronger negative effect on the mental health of female or rural middle-aged and older adult caregivers. The mechanism analysis shows that spousal care affects the mental health by reducing the number of weekly exercise and increasing the family’s non-food expenditure.ConclusionThe provision of spousal care in the middle-aged and older adult groups does harm the mental health of caregivers. Vulnerable groups such as families in which both spouses need care, female or rural caregivers expect more attention and support.